Предмет: Алгебра,
автор: Farzullaev
Найдите значение выражения:((b+3):(a-2))*(-4) при a=-5 b=6
Ответы
Автор ответа:
1
((6+3):(-5-2))*(-4)=(9:(-7))*(-4)=1 2/7 *(-4)=-4 1/7
Автор ответа:
1
28 будет
Тоесть ((6+3):(-5-2))*(-4)
Минус на минус даёт плюс.
Ответ 28
Тоесть ((6+3):(-5-2))*(-4)
Минус на минус даёт плюс.
Ответ 28
Farzullaev:
Спосибо!
Похожие вопросы
Предмет: Геометрия,
автор: ku8112710
Предмет: Алгебра,
автор: GAMLETEPREMAN
Предмет: Биология,
автор: azr2000e
Предмет: Математика,
автор: aaddeellaaiidda
Предмет: Математика,
автор: tamillaqasimov